TiO2@g-C3N4 core/shell spheres with uniform mesoporous structures for high performance visible-light photocatalytic application. Issue 15 (15th October 2019) - Xia, Yi; Xu, Lei; Peng, Jinghui; Han, Jiazheng; Guo, Shenghui; Zhang, Libo; Han, Zhaohui; Komarneni, Sridhar
Abstract: Mesoporous g-C3 N4 nanosheets (MCN) with uniform pore size were utilized to decorate mesoporous TiO2 spheres (TSs) to form a core-shell heterojunction photocatalyst containing uniform mesopores. Moreover, the mesoporous g-C3 N4 nanosheets served as shells for composites, in addition to playing a pivotal function for the regulation of the pore structure of the composite. The mesoporous TiO2 @g-C3 N4 core/shell structure having a uniform pore size exhibited high surface area of ∼134 m 2 /g. This coupled material with improved porosity, not only led to increased visible-light absorption but also led to the enhanced charge generation/separation. In addition, it showed a lengthy cycling stability with highly active visible-light efficiency to degrade Rhodamine B (RhB) dye.